Utopiska strategier i Christine de Pizans Kvinnostaden - Franzén, Carin (K&K - Kultur og Klasse, 2012)
UTOPIAN STRATEGIES IN CHRISTINE DE PIZAN’S CITY OF LADIES | Christine de Pizan’s appropriation of the dominant literary discourse in the later Middle Ages is an innovative reworking of established models, especially that of the configuration of women in the two directions of idealization and debasement. In the article I assess the strategies Christine develops to counteract this dialectic in order to open a newM– utopianM– discursive space for female subjectivity. My examples are mainly taken from Le Livre de la Cité des Dames (1404-1405). Late medieval representations of women incorporate a radical change from the idealization of the Lady and love in courtly literature into a more explicit misogynistic configuration, which can be seen for example in Le Roman de  la Rose (c. 1230). I argue that Christine responds to this change by a disclosure of this ambiguous discourse towards what it represses, i.e. a cultural unconscious of violent and incestuous dramas.